2018
DOI: 10.3892/ijmm.2018.3663
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‑34a inhibits oxidized low‑density lipoprotein‑induced apoptosis and oxidative stress in human umbilical vein endothelial cells

Abstract: Oxidized low‑density lipoprotein (ox‑LDL) promotes endothelial cell dysfunction, which is a primary risk factor for the development of atherosclerosis. A previous study reported that microRNA (miRNA/miR)‑34a is upregulated in atherosclerotic samples. However, its function and underlying mechanisms remain to be fully elucidated. In the present study, miRNA microarray analysis was performed to investigate the miRNA expression profile in atherosclerotic plaque tissues and examine the role of miR‑34a in ox‑LDL‑ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…26 Moreover, downregulation of miR-34a suppressed Ox-LDL-induced apoptosis and oxidative stress in human umbilical vein endothelial cells. 27 However, the role of miR-34a in Ox-LDL stimulated macrophages is still unclear. Hence, we further explored whether metformin promoted proliferation and suppressed apoptosis in Ox-LDL stimulated macrophages through regulating miR-34a expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Moreover, downregulation of miR-34a suppressed Ox-LDL-induced apoptosis and oxidative stress in human umbilical vein endothelial cells. 27 However, the role of miR-34a in Ox-LDL stimulated macrophages is still unclear. Hence, we further explored whether metformin promoted proliferation and suppressed apoptosis in Ox-LDL stimulated macrophages through regulating miR-34a expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that metformin could down-regulate miR-34a expression in high glucose condition and downregulation of miR-34a could suppress Ox-LDL-induced apoptosis. 26,27 Hence, we presumed that metformin may promote proliferation and suppressed apoptosis in Ox-LDL stimulated macrophages through regulating miR-34a expression. To conrm whether the pro-proliferation and antiapoptosis effect of metformin was mediated by miR-34a, we rst detected miR-34a expression in macrophages with Ox-LDL and metformin treatment.…”
Section: Mir-34a Overexpression Reversed the Effects Of Metformin On mentioning
confidence: 98%
See 1 more Smart Citation
“…There is growing evidence that miRNAs control these pathologic processes including endothelial dysfunction (miR let-7g, mir-17-3p, miR-31, miR-146a, miR-155, miR-181 family, miR-221/-222,) [170][171][172][173][174][175], oxidative stress (miR-let-7a/b, miR-19b, miR-20a, miR-98, miR-126, miR-142-3p, miR-199a-3p and -5p, miR-200c, miR-221, miR-222, miR-328) [176][177][178][179][180][181][182][183][184][185][186][187][188][189], monocyte recruitment, differentiation and activation (miR-21, miR-23a-5p, miR-27a/b, miR-33, miR-34, miR-146a, miR-155, miR-212, miR-451, miR-590, miR-758-5p, [190][191][192][193][194][195][196][197][198][199][200][201] and inflammation/secretion of inflammatory cytokines (miR let-7g, miR-17-3p, miR-31, miR-146a, miR-155, miR-181a-3p/-5p, miR-181b, miR-221 and miR-222) [171,202,203]. Interestingly, a number of them are simultaneously involved in all those processes, suggesting common and/or cooperative activities, and underlying their relevance in the physiopathology of CVD.…”
Section: Cellular Micrornas As Biomarkers Of Cardiovascular Disease Imentioning
confidence: 99%
“…Both miR-98 and let-7a/b inhibit LOX-1 expression, which prevents oxLDL uptake into the endothelium [64,65]. Conversely, miR-34 antagonises oxLDL cell injury by targeting the cell-survival gene bcl-2 [66].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%